2009
DOI: 10.3892/mmr_00000109
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide gene expression profiles of ovarian carcinoma: Identification of molecular targets for the treatment of ovarian carcinoma

Abstract: Abstract. This study aimed to clarify the molecular mechanisms involved in ovarian carcinogenesis, and to identify candidate molecular targets for its diagnosis and treatment. The genome-wide gene expression profiles of 22 epithelial ovarian carcinomas were analyzed with a microarray representing 38,500 genes, in combination with laser microbeam microdissection. A total of 273 commonly up-regulated transcripts and 387 down-regulated transcripts were identified in the ovarian carcinoma samples. Of the 273 up-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…CHMP4C is involved in the final steps of cell division, co-ordinating midbody resolution with the abscission checkpoint 13 and its transcription is regulated by TP53 to enhance exosome production 14 . A more recently study has shown that CHMP4C is frequently overexpressed in ovarian tumor tissues, with the suggestion that it may represent a diagnostic tumor marker and therapeutic -target for patients with the disease 15 .…”
Section: Resultsmentioning
confidence: 99%
“…CHMP4C is involved in the final steps of cell division, co-ordinating midbody resolution with the abscission checkpoint 13 and its transcription is regulated by TP53 to enhance exosome production 14 . A more recently study has shown that CHMP4C is frequently overexpressed in ovarian tumor tissues, with the suggestion that it may represent a diagnostic tumor marker and therapeutic -target for patients with the disease 15 .…”
Section: Resultsmentioning
confidence: 99%
“…SLC16A14 belongs to the group of monocarboxylate transporters 38 . It is downregulated in ovarian tumors compared to normal tissues 39 , and it is related to drug resistance of ovarian cancer cells in vitro 11 . We did not corroborate the role of SLC16A14 in drug resistance of ovarian cancer; however, we found association of high SLC16A14 expression level with longer PFS.…”
Section: Discussionmentioning
confidence: 99%
“…Its protein expression was mostly reduced in various pancreatic ductal adenocarcinomas compared with normal ducts (Li et al, 2008). Another ESCRT-III subunit, Chmp4C, was frequently overexpressed in ovarian carcinoma tissue, and not expressed in control tissues (Nikolova et al, 2009). Genome wide association studies identified Chmp4C as a candidate susceptibility gene contributing to an excess familial risk to epithelial ovarian cancers (EOC) and found it to be overexpressed in two epithelial ovarian cancer cell lines and in primary EOC tissues (Pharoah et al, 2013).…”
Section: Tumor Samplesmentioning
confidence: 99%